MEDIA PEMBELAJARAN INTERATIF SENI BUDAYA PADA SMK DB 4 KOTA JAMBI: Adobe flash CS6;Cultural Arts;Learning Media. - Megawati, Merti; -, Nilawati; -, Riswan (JURNAL AKADEMIKA, 2020)
Schools are institutions for the teaching of students under the supervision of teachers. In formal education schools which are generally compulsory, in this system students go through a series of teaching and learning activities in schools. In a school there is a cultural arts course. To assist students in improving their understanding of the material conveyed by the teacher, using interactive learning media which is currently very developed in the world of education. That way the researchers are interested in making Interactive Learning Media for Cultural Arts at SMK DB 4 Jambi City. By using the Adobe Flash Professional CS6 application, Adobe After Effects with evaluation. This learning media application can help students in the learning process.